African slavery in Portuguese India: Goa in the 16th and 17th centuries - Hofbauer, Andreas [UNESP] (UNISINOS - Universidade do Vale do Rio Dos Sinos, 2023)
The article seeks to show how, in parallel with the emergence of a slaveholding society in Brazil, the Portuguese colonial intervention in India also led to the constitution of a society marked by the presence of slaves. It seeks not only to point to the multiple convergences and similarities, but also to understand the contexts and practices that distinguished the phenomenon of slavery in Goa from that of the New World.
Escravidão africana na Índia portuguesa: Goa nos séculos XVI e XVII
Keywords: African Diaspora; India; slavery